2013
DOI: 10.1182/blood-2012-06-435644
|View full text |Cite
|
Sign up to set email alerts
|

Human plasmacytoid dendritic cells efficiently cross-present exogenous Ags to CD8+ T cells despite lower Ag uptake than myeloid dendritic cell subsets

Abstract: Key Points• Cross-presentation of both soluble and cell-associated tumor antigens by human DC subsets is enhanced by addition of adjuvant TLR agonists. • Ability to cross-present exogenous antigen with high IFN␣ secretion puts human pDCs as activators of CD8 ϩ T cells in antitumor responses. IntroductionDendritic cells (DCs) are the professional antigen presenting cells (APCs) of the immune system with the unique capacity to attract and activate naive CD4 ϩ and CD8 ϩ T cells. 1 After infection or inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
153
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 157 publications
(159 citation statements)
references
References 49 publications
(83 reference statements)
3
153
1
2
Order By: Relevance
“…However, for a potent antitumor response, both CD4 + and CD8 + T cell activation is essential. Although human pDCs were previously thought to poorly cross-present exogenous Ag to CD8 + T cells, accumulating evidence now suggests that human pDCs are endowed with an efficient cross-presenting machinery (9)(10)(11)(12)(13)(14). Just recently, we could demonstrate the potency of pDCs in a small cohort of metastatic melanoma patients, in whom vaccination with activated pDCs induced favorable immune responses and significantly extended overall survival (15).…”
mentioning
confidence: 64%
“…However, for a potent antitumor response, both CD4 + and CD8 + T cell activation is essential. Although human pDCs were previously thought to poorly cross-present exogenous Ag to CD8 + T cells, accumulating evidence now suggests that human pDCs are endowed with an efficient cross-presenting machinery (9)(10)(11)(12)(13)(14). Just recently, we could demonstrate the potency of pDCs in a small cohort of metastatic melanoma patients, in whom vaccination with activated pDCs induced favorable immune responses and significantly extended overall survival (15).…”
mentioning
confidence: 64%
“…In vitro studies have already demonstrated that human mDCs and pDCs synergize via bidirectional cross-talk (11,42). Addition of CD141 þ myeloid DCs may even further improve the potency of DC vaccines, as CD141 þ DCs are highly efficient in antigen cross-presentation to CD8 þ T cells and are able to secrete IFNg and IL12 upon activation, which allows the effective induction of T helper 1 and CTL responses (43)(44)(45)(46)(47)(48). However, the limited presence of DCs in blood and lack of GMPgrade isolation reagents currently impedes the use of CD141…”
Section: Discussionmentioning
confidence: 99%
“…On pDCs, CD40 ligation has been described to augment the production of IL-6, thereby facilitating generation of antibody producing plasma cells (Jego et al, 2003). Furthermore, CD40 signaling can aid effective activation of T cells or prevent T cell exhaustion (Krug et al, 2001;Fonteneau et al, 2003;Tel et al, 2013;Fuse et al, 2009;Isogawa et al, 2013). In CHB patients low and exhausted T cells are consistently observed and held responsible for the inability to clear HBV (Ferrari et al, 1990;Jung et al, 1991;Boni et al, 2007Boni et al, , 2012Bertoletti and Ferrari, 2016).…”
Section: Discussionmentioning
confidence: 99%